PANDANGAN HAKIM TERHADAP ISBAT NIKAH SIRI PRA UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DI PENGADLAN AGAMA MALILI KELAS II - Hakiki; Qadir Gasing; Siti Nurul Fatimah Tarimana (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2022)
The main problem in this research is the judge's view on the pre-law isbat siri marriage number 1 of 1974 concerning marriage in the Malili religious court class II (case study decision number 52/Pdt.G/2020/PA.Mll. The sub-problems are, what is the background of the application for pre-law siri marriage isbat number 1 of 1974 concerning marriage and then how is the judge's consideration in giving decisions in pre-law serial marriage isbat number 1 of 1974 concerning marriage in the decision of case number 52/Pdt.G/ 2020/PA.Mll. The type of research used is qualitative with the method of obtaining data directly through interviews. The results of this study are, the reasons for the application for isbat marriage siri in the case decision 52/Pdt.G/2020/PA.Mll, namely solely The eyes of the plaintiff (wife, Nurcaya) want to get a legality of their marriage and get a marriage certificate because the marriage is not registered with the KUA with the purpose of managing the husband's pension (late. Manga Saleh) who used to work as a civil servant at the Maros Forestry Service, apart from that the judge's consideration in deciding the siri marriage isbat case by stating that the plaintiff's marriage to Manga Saleh which took place before Law Number 1 of 1974 concerning marriage was later married. does not conflict with the pillars and conditions of marriage that have been determined as stipulated in article 14 to article 29 of the compilation of Islamic law and is in accordance with the provisions of article 39 to article 44 of the KHI. The implication of this research is a suggestion for judges who handle the application for the isbat of unregistered marriages to be more considerate in granting the case because with this it can make people not arbitrarily in carrying out unregistered marriages.